Effect of source location on contaminant dispersion pattern and occupants inhaled air quality in lecture room under displacement ventilation - Aya Essa; Toshio Yamanaka; Tomohiro Kobayashi; Narae Choi (Japan Architectural Review, 2023)
Abstract Displacement ventilation (DV) is considered an energy saving air conditioning system and is especially recommended for classrooms for providing cool clean air in the occupied zone. However, in the current pandemic situation, ventilation systems should be assessed in terms of infection‐spread prevention as well. Hence, this study aims at assessing the efficiency of displacement ventilation in minimizing infection spread in lecture halls through investigating the effect of source position on the contaminant concentration distribution. The settings of a mid‐size DV lecture hall in Osaka University, Japan was chosen as a case‐study. Ten single‐contaminant‐source cases were simulated using CFD software. The cases were analyzed in terms of temperature distribution, contaminant diffusion pattern and vertical distribution, and breathing air quality using indices, such as local air quality index and scale of ventilation efficiency. The results demonstrated a considerable variation between cases in terms of contaminant distribution pattern, number of occupants affected, average inhaled‐air quality, and diffusion radius. Accordingly, given the ventilation system design, best and worst case‐scenarios were pointed out and factors affecting the variation were highlighted and further investigated to conclude the impact of each factor.